Plasmodium vivax Protein PvTRAg23 Triggers Spleen Fibroblasts for Inflammatory Profile and Reduces Type I Collagen Secretion via NF-κBp65 Pathway - Zhang, Hangye; Shen, Feihu; Yu, Jiali; Ge, Jieyun; Sun, Yifan; Fu, Haitian; Cheng, Yang (Frontiers in Immunology, 2022)
Plasmodium vivax is the most widespread human malaria parasite. The spleen is one of the most significant immune organs in the course of malaria infection, and it contains splenic fibroblasts (SFs), which supports splenic immunologic function by secreting type I collagen (collagen I). Plasmodium proteins have rarely been found to be involved in collagen alterations in the spleen during malaria infection. Here, we selected the protein P. vivax tryptophan-rich antigen 23 (PvTRAg23), which was expressed by the spleen-dependent gene Pv-fam-a of P. vivax. The protein specifically bound to cells with vimentin as receptors.. However, such collagen changes were not mediated by binding to vimentin, but rather activating the NF-κBp65 pathway to produce inflammatory cytokines. Collagen impaired synthesis accompanied by extracellular matrix-related changes occurred in the spleen of mice infected with P. yoelii 17XNL. Overall, this study is the first one to report and verify the role of Plasmodium proteins on collagen in HSF in vitro. Results will contribute to further understanding of host spleen structural changes and immune responses after malaria infection.